Metabolomics reveal root differential metabolites of different root-type alfalfa under drought stress - Wang, Kun; Nan, Li-Li; Xia, Jing; Wu, Shi-Wen; Yang, Li-Li (Frontiers in Plant Science, 2024)
Introduction Alfalfa (Medicago sativa L.) is the favored premium feed ingredient in animal husbandry production which is in serious jeopardy due to soil moisture shortages. It is largely unknown how different root types of alfalfa respond to arid-induced stress in terms of metabolites and phytohormones. Methods Therefore, rhizomatous rooted M. sativa ‘Qingshui’ (or QS), tap-rooted M. sativa ‘Longdong’ (or LD), and creeping rooted M. varia ‘Gannong No. 4’ (or GN) were investigated to identify metabolites and phytohormones responses to drought conditions. Results We found 164, 270, and 68 significantly upregulated differential metabolites were categorized into 35, 38, and 34 metabolic pathways in QS, LD, and GN within aridity stress, respectively. Amino acids, organic acids, sugars, and alkaloids were the four categories of primary differential metabolites detected, which include 6-gingerol, salicylic acid (SA), indole-3-acetic acid (IAA), gibberellin A4 (GA4), abscisic acid (ABA), trans-cinnamic acid, sucrose, L-phenylalanine, L-tyrosine, succinic acid, and nicotinic acid and so on, turns out these metabolites are essential for the resistance of three root-type alfalfa to aridity coercing. Discussion The plant hormone signal transduction (PST) pathway was dramatically enriched after drought stress. IAA and ABA were significantly accumulated in the metabolites, indicating that they play vital roles in the response of three root types of alfalfa to water stress, and QS and LD exhibit stronger tolerance than GN under drought stress.